An Electrochemical Method for Fast and Controlled Etching of Fluorine-Doped Tin Oxide Coated Glass Substrates. Issue 2 (1st January 2017) - Koiry, S. P.; Jha, P.; Veerender, P.; Sridevi, C.; Debnath, A. K.; Chauhan, A. K.; Muthe, K. P.; Gadkari, S. C.
Abstract : Fluorine-doped tin oxide (FTO) coated glass substrates are etched by a mixture of Zn and HCl for solar cells, flat panel displays, and related applications. However, this chemical etching method has its own limitations, and the most important limitation is no control on the etching process. Here, we report a controlled etching of FTO-coated glass substrate by a chronoamperometric method. In this method, optimized step potentials, −3 V for 10 s, −5 V for 80 s and −9 V for 10 s are applied between the FTO substrate to be etched and a counter electrode dipped in acidic 0.1 M FeCl3 (aq) electrolyte. The etched FTO was characterized by the energy dispersive X-ray spectroscopy showing complete removal of conducting FTO layer that was further studied by current-voltage characteristics. The chemical reaction involved in this etching process was investigated by the X-ray photoelectron spectroscopy that reveals similar chemical reaction as reported for the chemical method.